Development of Mobile Learning Based Electronic Student Worksheets to Measure Learning Motivation on Sensing Systems Materials - Fitria Lafifa*; Dadan Rosana; Jumadi Jumadi; Mirsya Adelia (Universitas Syiah Kuala, 2022)
The material of the sensory system is important because in the sensory system there are several kinds of senses and the nervous system which is still abstract and the problem that occurs is a misconception about the material. Motivation is one of the factors that support success in learning, but students learning motivation is still low. This study aims to produce valid and feasible mobile learning-based electronic student worksheets and to measure students learning motivation on sensing system materials. The research subjects were students of class VIII MTsN 8 Banyuwangi. This study uses Research and Development methods and 4D models with 4 stages, namely define, design, develop, and dissemination. The instrument used was a material validation questionnaire, medial, readability, and students' learning motivation. The validation results show the average percentage of the material test is 94% and the media is 94% with very feasible criteria. The percentage of the students' readability test has an average value of 71% with a good category and the students' learning motivation is very strong with a percentage of 82%. Thus, electronic student worksheets can measure students' learning motivation. For future researchers, it is recommended to use the product in classroom learning